Bread and roses, too [compact disc, unabridged] - Paterson, Katherine (Listening Library, 2006)
Jake and Rosa, two children, form an unlikely friendship as they try to survive and understand the 1912 Bread and Roses strike of mill workers in Lawrence, Massachusetts.